Culture and poverty: a case study of a girl with special educational needs from a poor community in South India - Philip, Neetha (Support for learning, 2015)
Girls with disabilities from lower economic homes are disadvantaged (in terms of gender, disability and poverty) in India, and are often regarded as useless by their communities. There is a need to improve and provide a chance for self‐sufficiency among women with disabilities in India. The purpose of this study was to examine the life‐chances (i.e. the likelihood of living a self‐sufficient life) of girls with disabilities in rural India and subsequently suggest ways through which one can improve these life chances. The study was a single‐case study that used data from semi‐structured interviews carried out in rural Bangalore. It was found, based on the interviews and available literature on the issue, that women with disabilities are at a disadvantage, especially those in rural settings. The most significant factors that seem to affect the life chances of the subject in the study were parental hesitation, a lack of opportunities and low self‐esteem and confidence. The study suggests awareness programmes, counselling and the implementation of home‐based education services as some ways through which the life‐chances of girls with disabilities are likely to improve.